Andean blueberry (vaccinium meridionale swartz) seed storage behaviour characterization under low temperature conservation / categorización del comportamiento de las semillas de mortiño (vaccinium meridionale swartz) en almacenamiento a baja temperatura (2012)
A study was conducted to categorize harvest stage, maximun dry weigth and tolerance to desiccation at low temperature storage of seeds of the promising species “andean blueberry”, Vaccinium meridionale Swartz. The aim was to determine the long term conservation possibility of a duplicate of the current Colombian Andean Highland field collection in cool storage rooms, as well as that of newly collected local populations from the mentioned highland region, which are in danger of genetic erosion due to human intervention and the ongoing global climate change. Both maximum dry weight and the highest germination percentages were observed to be associated in seeds extracted from deep purple (fully ripe) berries. The seeds exhibited orthodox storage behavior, which indicates the possibility for long-term cold storage of a duplicate of the current metapopulation of the species in the country. / Se realizó un estudio para categorizar el estado de cosecha, máximo peso seco de la semilla y la tolerancia de ésta a la desecación y almacenamiento a bajas temperaturas, en la especie promisoria mortiño, Vaccinium meridionale Swartz. El objetivo fue establecer el potencial de conservar un duplicado de la colección de campo y rescatar y almacenar poblaciones espontáneas de la zona alto andina colombiana, en peligro de pérdida por intervención humana y el cambio climático, que pueden causar erosión de la diversidad genética de la especie. El máximo peso seco se logró a partir de semillas extraídas de bayas de color morado oscuro, con obtención de germinación superior en éstas y una relación directa entre el peso seco y el porcentaje de germinación. La semilla exhibió comportamiento ortodoxo, lo cual indica la posibilidad de almacenamiento a largo plazo de un duplicado de la metapoblación de la especie, existente en el país.